"That is why I gave in to age my competitive ability but not my soul!" : a spiritual journey in endurance running - Ronkainen, Noora (2011)
In this article, I explore the spiritual dimensions of running. I draw on theological and existential perspectives, athletic career research as well as post-sport ideologies to construct a multi-voiced representation of the spiritual meanings of endurance running current in Finnish running culture(s). Through narrative, analysis, reflexivity, interpretation and theorizing this study aimed to gain a deeper understanding of how distance runners negotiate dominant discourses on sport and exercise in the process of making running meaningful to them.